Analisis Gaya Belajar Siswa dengan Prestasi Belajar Rendah Di Kelas V SDN Kelurahan Rawajati - Miftakhul, Laras, Alifia Najma Sholikha, Fanny Yustia Zahra (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
Learning styles influence how students receive information from teachers in learning activities. Student learning achievement can be influenced by whether the student's learning style is met. This research aims to analyze variations in learning styles of students with low learning achievement in class V of SDN Rawajati 07 Pagi. This research was conducted using a qualitative descriptive method, by detailing and describing a student learning styles. The research results indicate that out of 10 students with low academic achievement in class V of SDN Rawajati 07 Pagi, the majority has a visual learning style (34.9%), followed by an auditory learning style (32.5%) and a kinesthetic learning style (32.5%). There are 4 students with a visual learning style, 2 students with a kinesthetic learning style, 1 student with a combination of visual and kinesthetic learning styles, and 1 student with a combination of visual and auditory learning styles. Learning can be facilitated through various strategies, one of which is implementing differentiated instruction. Besides teachers, it is also important for families to be aware of their children's learning styles, as this helps them prepare a conducive learning environment for the students.